Design and Implementation of a Shunting Communication Voice Recorder at Tegal Station Using Visual Basic - dewi, firda; Faisal Rachman, Natriya; Prasetyo, Agustinus (SAINSTECH NUSANTARA, 2024)
Communication between the two is done using a handy talky. Communication between langsir officers and train travel organizers is one of the most influential communications in train operations. In (PM No. 45 of 2018) concerning the technical requirements of railway telecommunications equipment, it is stated that at least lansiran communication meets the operating system requirements, every conversation must be recorded. There is currently no recording device for alert communication at Tegal station, while the alert process at Tegal station occurs at least 8 times a day.In this study, an application was made to record the voice of the langsiran communication to record all communications made by the langsir officer and the train travel controller. By taking voice data from the handy talky which is used as a master, then it is connected using a series of interfaces via a cable jack on a PC that has installed a voice recording application for langsiran communication that has been made with Microsoft Visual Studio. The recorded data that has been obtained is processed and stored in a MySQL database with the phpMyAdmin interface.From the test results, the designed software can be run properly, can automatically record alert communication, the stored data can be searched based on the recording code and recording date, and the recorded recordings can be played back and show the recording time